Adhesive Categories - Lack, Stephen; Sobocinski, Pawel (BRICS Report Series, 2003)
We introduce adhesive categories, which are categories with structure ensuring that pushouts along monomorphisms are well-behaved. Many types of graphical structures used in computer science are shown to be examples of adhesive categories. Double-pushout graph rewriting generalises well to rewriting on arbitrary adhesive categories.